Association between intimate partner violence against women and chronic malnutrition among children under 5 years of age: Analysis of the 2020 Demographic and Family Health Survey in Peru - Arrascue , Joaquín (2023)
Introduction: The association between intimate intimate partner violence against women and chronic malnutrition in children has not been clearly established. Many conceptual frameworks of child malnutrition do not considered domestic violence as a determinant. Objective: To evaluate the association between intimate intimate partner violence against women and chronic malnutrition in children under 5 years of age. Methods: We conducted a study of secondary data based on the Demographic and Family Health Survey 2020 of Peru. We estimated the odds ratio crude and adjusted with a binary logistic regression that considered as exposure to intimate intimate partner violence and dependent variable to chronic malnutrition, also we included 16 covariates of interest selected from the relevant literature. Results: We included data from 8980 women and their children. The chronic malnutrition prevalence in children under 5 months of age was 10.7% (95% CI 9.8 to 11.7). We found no association between chronic malnutrition in children and emotional violence (aOR: 0.98, 95% CI: 0.72 to 1.32), severe physical violence (aOR: 1.02, 95% CI: 0.62 to 1.68), and sexual (aOR: 0.94, 95% CI: 0.50 to 1.77) against mothers. Conclusions: These results add to the evidence that supports the absence of association between the three types of intimate partner violence as risk factors of chronic malnutrition in children under 5 years of age and highlight the importance of other variables such as the mother's educational level.